Implementation Regarding The Competencies of Vocational High School Graduates in The Meta-System-Networking (MSN) Model Approach in Jayapura District, Papua Province - Tri Bowo Budi Santoso; Tjahya Supriatna; Khasan Efendi; Dewi Sulistyani (JURNAL AKTA, 2025)
This study examines the implementation of competency policies for Vocational High School (SMK) graduates in Jayapura Regency using the Mental-System-Networking (MSN) approach (Kadji, 2016). This approach emphasizes the importance of synergy between the government, the business world, and the community in improving the competence of SMK graduates according to the needs of the world of work. The research method used was a quantitative approach with a sample of 252 respondents. The results showed that the implementation of MSN-based policies has a significant influence on the competence of SMK graduates.  The MSN approach is effective because it considers mental factors, systems, and integrated networks. Mental factors contribute the most to improving competence, followed by systems and networks. The results of this study also show that the implementation of stake-holders from the business world and the industrial world (private sector) makes the largest contribution to the competence of SKM graduates so that strategic collaboration between schools, industry and the community to overcome the challenges of vocational education in the regions, especially in Jayapura Regency. Thus, the MSN approach can be a relevant framework in improving the competitiveness of SMK graduates in the local and global job market.